Analytical approximate solution of fractional order smoking epidemic model. (September 2022) - Günerhan, Hatıra; Rezazadeh, Hadi; Adel, Waleed; Hatami, Mohammad; Sagayam, Kulandairaj Martin; Emadifar, Homan; Asjad, Muhammad Imran; Hamasalh, Faraidun K; Hamoud, Ahmed A
In this paper, the fractional smoking epidemic model is presented. The model is presented in terms of Caputo's fractional derivation. The fractional differential transformation method (FDTM) is presented to find an approximate analytical solution to the model. The method is tested on the model and the solution is compared with the homotopy transform method. The method shows the form of fast converging series and the results prove the applicability of the proposed technique, which gives accurate results.